(untitled) (Nuntius Antiquus, 2011)
This paper intends to show the importance of Eros in the Epodes. First of all, it is necessary to study the structure of the book: in the first part (1-10), ten poems in a combination of iambic lines (an iambic trimeter followed by an iambic dimeter); in the second part (11-17), seven poems in various combinations. In this part, when the poet introduces new meters, Eros appears in the book and conquers the poet, modifying the poetry.